2018
DOI: 10.1002/ijc.31362
|View full text |Cite|
|
Sign up to set email alerts
|

Common dietary patterns and risk of cancers of the colon and rectum: Analysis from the United Kingdom Women's Cohort Study (UKWCS)

Abstract: Few prospective cohort studies in the UK have specifically focused on the associations between commonly consumed dietary patterns and colorectal cancer (CRC). The aim of our study was to assess whether red meat, poultry, fish and vegetarian dietary patterns are associated with differences in the incidence of cancers of colon and rectum in the UKWCS. Four common dietary patterns were defined based on a hierarchy of consumption of red meat, poultry and fish for each cohort participant, using a 217‐item food freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In addition, we collected data on admissions and costs by patients with colon cancer diagnosis to compare our findings about myeloma against those of a more prevalent cancer. Colon cancer was chosen as a comparator as it also affects both women and men, its economic burden has been extensively investigated [14,15] and its ICD-10 codes have been validated in previous studies using HES APC [16,17]. ICD-10 codes used to extract data on colon cancer admissions were “Malignant neoplasms of the colon” (C18), of the rectosigmoid junction (C19), and of the rectum (C20).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we collected data on admissions and costs by patients with colon cancer diagnosis to compare our findings about myeloma against those of a more prevalent cancer. Colon cancer was chosen as a comparator as it also affects both women and men, its economic burden has been extensively investigated [14,15] and its ICD-10 codes have been validated in previous studies using HES APC [16,17]. ICD-10 codes used to extract data on colon cancer admissions were “Malignant neoplasms of the colon” (C18), of the rectosigmoid junction (C19), and of the rectum (C20).…”
Section: Methodsmentioning
confidence: 99%
“…We created a detailed classification of the dietary patterns involved according to the principles mentioned in the incorporated eligible article (Supplementary Table 5). Classification resulted in 14 articles on vegan diets (21,22,25,28,29,31,35,36,39,43,47,51,54,57), 8 articles contained semivegetarian diets (24,32,37,38,41,48,61,63), 1 article was on pesco-vegetarians ( 27), 1 study mentioned lacto-ovo-vegetarians (55), 2 studies reported on pesco-laco-ovo-vegetarians (46,53), 1 study involved lacto-vegetarians (68), 10 articles were on prudent diets (23,26,27,30,34,44,56,58,60,62), 3 studies referred to the DASH diet (56,65,66) and 11 articles were on the Mediterranean diet (33,40,42,45,49,50,52,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the world’s third most common cancer and the fourth most deadly cancer, with almost 900,000 deaths annually [ 1 , 2 ]. In addition to a genetic background, it has been shown that metabolic profile [ 3 ], lifestyle [ 4 ], dietary habits [ 5 , 6 ], and smoking [ 4 , 7 ] are strongly and independently associated with colorectal polyps, the direct precursors of CRC. Moreover, smoking and dietary factors have been reported to interact in their association with colorectal neoplasia [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%